Chinese Soft-Shelled Turtle Oil in Combination With Swimming Training Improves Spatial Memory and Sports Performance of Aging Rats - Yang, Chia-En; Yeh, Tsung-Ming; Chang, Ching-Dong; Shih, Wen-Ling (Frontiers in Physiology, 2021)
In this study, waste fat from the Chinese soft-shelled turtle was used as the raw material, and soft-shelled turtle oil (SSTO) was extracted by water heating. Analysis of the fatty acid composition of SSTO revealed that the oil contains more than 70% unsaturated fatty acids, of which more than 20% are omega-3 poly-UFAs. DPPH radical scavenging and cellular ROS assays confirmed that the reduction of oxidative stress of SSTO. In D-galactose induced aging rats, SSTO feeding alone or in combination with swimming training resulted in improved memory and physical strength. In addition, SSTO feeding with swimming intervention significantly increased the SOD level and maintained better blood pressure in the aged rats. The serum DHEAS and soleus muscle glycogen level were also highly correlated with SSTO feeding and sport training. In conclusion, the results of this study demonstrated that SSTO has the potential for development into a health food with anti-aging effects and further reduce health risks, which are stronger when combined with daily swimming exercise.